Preliminary data on the psychometric proprieties of the italian version of the reflective functioning questionnaire. (13th April 2021) - Zobel, S. Beomonte; Ciavolino, E.; Beyer, S.; Fonagy, P.
Abstract : Introduction: Assessing mentalizing abilities is a complex issue. Only recently an instrument assessing mentalizing capacity as a whole, the Reflective Functioning Questionnaire (RFQ), has been developed. Objectives: To reach the purpose of our study, we investigated the psychometric proprieties of the Italian version of the RFQ. Methods: The study was conducted on a sample including a group of violent offenders and a group of community participants. All subjects fulfilled the RFQ, the Personality Inventory for DSM-5 (PID-5) and the Aggression Questionnaire (AQ). Results: The theoretical model was defined and analysed by using Partial Least Squares–Path Modelling with high-order construct definition. Data showed good psychometric proprieties of the Italian version of the RFQ. Also, specific patterns of correlations were identified between the RFQ subscales and both PID-5 and AQ scores. Offenders significantly differed from controls only in relation to one subscale of the RFQ. Conclusions: Data supported the factorial structure of the RFQ found in the original validation study. Results also support the existence of a second-order variable, mentalizing, resulting from the convergence of hypomentalizing and hypermentalizing.